Are Creativity, L2 Motivation and Soft Skills Related? A Study in VET Students - Inmaculada Calero López; Margarita González-Peiteado; Beatriz Rodríguez-López (MDPI AG, 2024)
Vocational Education and Training (VET) studies aim to improve students' skills to carve their niche in the labour market. Speaking different languages, showing teamwork skills and creativity are among the skills most in demand by employers. Thus, understanding students' motivation and their perception of their teamwork skills and creativity level may help to identify their weaknesses and strengths and to develop educational programs adapted to the current demands. This research was conducted with 596 students of higher-level and intermediate Vocational Education who answered an online questionnaire in class. The answers were analysed to seek the link between the students' motivation, their manifested teamwork skills, and their perceived level of creativity. The results confirmed the positive correlation between the three of them. However, and despite the positive results, further empirical research is needed, especially to understand how motivation, soft skills and creativity develop and what kind of initiatives have an impact on these variables.